(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2024)
Religiously associated Manipuri Kombirei or Manipuri Iris which is considered endemic to Manipur as per the Flora of Manipur (2000) has long been misidentified (misnomer) as Iris bakeri Wall. (Iridaceae) but after thorough investigation the botanical identity of this plant has been established as Iris laevigata Fisch. In India, I. laevigata Fisch. is the first report from Manipur, hence it is a new addition to the Indian Flora. During 1960’s Kombirei plant was naturally growing in two wetlands of Manipur namely, Lamphelpat and Yaralpat but now it has completely vanished from its natural habitat due to various factors like habitat loss and invasion by weeds but a few hundred plants are maintained in captive farm at the periphery of Lamphelpat by a private cultural society viz., Ipathoukok. Currently, some plants are also recorded in small pockets from two wetlands of Manipur namely, Maibam Phumlou and Ikkop pat which is believed to have been established later by being brought down by the upstream rivers falling into the lakes. Manipuri Iris is religiously offered during the Manipuri New Year viz., Sajibu Cheiraoba as a symbol of eliminating caste system. Due to its habitat sensitivity, conservation of this plant should be prioritized, otherwise loss of this species from Manipur may lead to loss of a species from the Indian flora.